Paraparesis due to angio-neurotropic Gurltia paralysans in a domestic cat (Felis catus) and retrospective study on feline gurltiosis cases in South America - Gómez, Marcelo; Muñoz, Pamela; Moroni, Manuel; Mieres, Marcelo; Bernal, Valentina; Rosenfeld, Carla; Taubert, Anja; Hermosilla, Carlos (Frontiers in Veterinary Science, 2024)
The nematode Gurltia paralysans is a neglected angio-neurotropic parasite causing chronic meningomyelitis in domestic cats (Felis catus) as well as wild felids of the genus Leopardus in South America. Adult G. paralysans nematodes parasitize the leptomeningeal veins of the subarachnoid space and/or meningeal veins of the spinal cord parenchyma. The geographic distribution of G. paralysans includes rural and peri-urban areas of Chile, Argentina, Uruguay, Colombia and Brazil. This case reports on clinical and pathological findings of severe thrombophlebitis and meningomyelitis in a G. paralysans-infected domestic cat resulting in ambulatory paraparesis. Neurological examination of affected cat localized the lesions at the thoracolumbar (T3-L3) and lumbosacral (L4-Cd4) segments. Molecular and morphological characteristics of extracted nematodes from parasitized spinal cord veins confirmed G. paralysans. Additionally, data obtained from a questionnaire answered by cat owners of 12 past feline gurltiosis cases (2014)(2015) were here analyzed. Questionnaire collected data on age, gender, geographic location, type of food, hunting behavior, type of prey and other epidemiological features of G. paralysans-infected cats. Data revealed that the majority of G. paralysans-infected cats originated from rural settlements thereby showing outdoor life styles with hunting/predatory behaviors, being in close contact to wild life [i. e. gastropods, amphibians, reptiles, rodents, birds, wild felids (Leopardus guinia)] and with minimal veterinary assistance. Overall, the neglected angio-neurotropic G. paralysans nematode still represents an important etiology of severe thrombophlebitis and meningomyelitis of domestic cats living in endemic rural areas with high biodiversity of definitive hosts (DH), intermediary (IH), and paratenic hosts (PH). The intention of this study is to generate awareness among veterinary surgeons as well as biologists on this neglected feline neuroparasitosis not only affecting domestic cats but also endangered wild felid species of the genus Leopardus within the South American continent.